Use of linear low density polythene film for frozen fish packaging - Govindan, T.K., Srinivasa Gopal, T.K. Joseph, J. and (Fishery Technology, 2021)
Physical properties of linear low density polythene film of 60 gauge thickness and its suitability as packaging material in frozen fish industry was studied in comparison with conventional 100 gauge low density polythene film. Both were comparable in water vapor transmission rate both at 38°C and -20°C, overall migration test and :flexibility at low temperatures. ·Even though the tearing strength was inferior to the conventional one, it is of no significance in its use in frozen fish industry. The new film worked out to be more economical than the other one.